(3GdHQGeL GdJOQjHjI aj GdHMhK GdJQHhjI (B:s (3HfGFgG(B-(3JWHjbGJgG (B= Training programs in educational research : disgine and applications /s - (3THjH, eMehO eMeOs ((3GdbGgQI (B:s (3YGde GdcJH,s, 2019)
(3jJfGhd gPG GdcJGH cd eG jNOe GdHQGeL GdJOQjHjI aj GdHMhK GdJQHhjI hJVef GdcJGH aj GdaUd GdChd eaghe GdJOQjH hCgejJg hCgOGag hHYV GdedGMXGJ Ydi GdHQGeL GdJOQjHjI HjfeG JfGhd GdaUd GdKGfj efgLjI GdHMK aj GdHQGeL GdJOQjHjI hCSGdjH GdJOQjH GdCcKQ TjhYG, HjfeG Ted GdaUd GdKGdK Jbjje GdHQGeL GdJOQjHjI ef NdGd feGPL eNJdaI HjfeG JeVef GdaU GdQGHY feGPL JWHjbjI ef HQGeL JOQjHjI aj HMhK JQHhjI(B. s
(3bGFeI eUWdMGJ (B: (3UaMI (B319-322.s
(3jTJed Ydi HHdjhLQGajI(B.s
Keywords: (3GdJQHjIs -- (3HMhKs; (3GdJYdjes -- (3HMhKs